Bibliometric Review of Research on Green Farming Practices in the Period 2010–2024 - Veronica L. Tuhumena; Liz Yanti Andriyani; Ivonne Fitri Mariay; Nandini Ayuningtias; Syaifullah Rahim (Westscience Press, 2026)
This study presents a bibliometric review of research on green farming practices published between 2010 and 2024. Using data retrieved from the Scopus database and analyzed through VOSviewer, the study examines publication trends, collaboration networks, and thematic evolution within the field. The findings indicate a significant growth in scholarly output over the last decade, reflecting increasing global concern for sustainable agricultural transformation. Keyword co-occurrence analysis reveals that early research focused primarily on agronomic practices such as soil management, manure application, crop rotation, and yield improvement. Over time, the thematic orientation expanded toward broader sustainability issues, including climate change, biodiversity, food security, and environmental protection. Co-authorship and country collaboration networks highlight the central role of countries such as India, the United States, China, and several European nations in shaping the global research agenda. Overlay and density visualizations further demonstrate a shift from technical input management toward integrated sustainability and resilience frameworks. Overall, the study confirms that green farming research has matured into an interdisciplinary and policy-relevant domain that integrates agronomic innovation with global sustainability challenges.